Pengaruh Knowledge Management dan Talent Management terhadap Pengembangan Karir Karyawan - Hani Darmawati (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This study aims to; 1) To determine Knowledge Management in KPSBU Lembang; 2) To know Talent Management in KPSBU Lembang; 3) Knowing Employee Career Development in KPSBU Lembang. The sampling technique is saturated sampling. This research use descriptive and verification methods with the number of respondents as many as 67 people using data collection techniques in field research and library research. The result of this study concluded that; 1) Knowledge Management at KPSBU Lembang is included in the high category; 2) Talent Management at KPSBU Lembang is quite good; 3) Employee Career Development is quite good; 4) Knowledge Management affects Employee Career Development; 5) Talent Management affect Employee Career Development; 6) Knowledege Management and Talent Management affect Employee Career Development. In conclusion is a Knowledge Management and Talent Management based on Employee Career Development at KPSBU Lembang. Abstrak. Penelitian ini bertujuan untuk 1) Mengetahui Knowledge Management di KPSBU Lembang. 2) Untuk Mengetahui Talent Management di KPSBU Lembang. 3) Mengetahui Pengembangan Karir Karyawan di KPSBU Lembang. Teknik penarikan sampel adalah sampling jenuh. Penelitian ini menggunakan metode deskriptif dan metode verifikatif dengan jumlah responden sebanyak 76 orang menggunakan teknik pengumpulan, penelitian lapangan dan penelitian kepustakaan. Hasil penelitian ini menyimpulkan bahwa : 1) Knowledge Management di KPSBU Lembang termasuk kategori Tinggi; 2) Talent Management di KPSBU Lembang cukup baik; 3) Pengembangan Karir Karyawan di KPSBU Lembang cukup baik; 4) Knowledge Management berpengaruh signifikan terhadap Pengembangan Karir Karyawa; 5) Knowledge Management berpengaruh terhadap pengembangan karir karyawan 6) Talent Management berpengaruh terhadap Pengembangan Karir Karyawan. Kesimpulannya terdapat pengaruh antara Knowledge Managenet dan Talent Managent terhadap Pengembangan Karir Karyawan.